Implementation of Project -Based Learning Model (PjBL) Using STREAM-Based Approach in Elementary Schools (Universitas Negeri Semarang, 2020)
Learning in 21st Century focuses on the development of students learning activities in order to increase their creativity through creative products. This study aims to describe the implementation of Project-based Learning model using STREAM-based approach (Science, Technology, Religion, Engineering, Art, and Mathematics) on students learning activities and the results of creative products made by students. The research method used was descriptive qualitative. The data source was chosen using purposive sampling technique. The research subjects are 3 elementary schools in Banjarmasin city, amounting to 80 students. Data collection techniques were done through observation and product assesment. The results showed that the implementation of the PjBL model using STREAM-based approach had an effect on increasing the result of students learning up to 92.1 (very good), and their activeness in learning activities made them become more creative in designing an interesting product. In this study there were 4 creative products created by the students namely drip irrigation, water cycle, water quality test, and religious-based picture story booklets. The implication of this research is a great opportunity for teachers in elementary schools to use PjBL model using STREAM-based approach in order to increase students’ interest, creativity, and social attitudes in learning.